REFLEKSI HUBUNGAN MANUSIA DAN TUHAN DALAM HINDU MENURUT PLATO - Kadek Yuli Wahyu Astini; Astu Arya Putra (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2019)
Plato is one of the famous philosophies. Many theories were created by Plato, which began only in ideas that developed and became knowledge, so that at this time Plato's view became a reference for scholars in the world. One of them is about divinity. In this article the author will share information on how reflection of human and God relations in Hinduism according to Plato. The concept of Plato's view of divinity and mankind, has a relationship and is related to the concepts that exist in the teachings of Hinduism. So in the teachings of Hinduism having similarities with the teachings or views given by Plato, only the term or language used is different. Where God is the creator and man consists of two elements, namely soul and body in Plato's view, but in the Hindu concept of God is Brahman and humans consist of three layers, one of which has the same characteristics as God. The conclusion in this article is what and how the results of the reflection of human relations with God in Hinduism according to Plato.Key words : Idea, Brahman, Atman, Moksa